2019
DOI: 10.3906/zoo-1902-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, ultrastructural, and molecular identification of a new microsporidian pathogen isolated from Crepidodera aurata (Coleoptera, Chrysomelidae)

Abstract: A new microsporidian pathogen isolated from Crepidodera aurata was identified based on morphological and ultrastructural characteristics, coupled with a molecular phylogenetic analysis. The spores of the microsporidian pathogen were slightly curved in shape, and measured 2.44-3.55 µm in length and 1.25-1.55 µm in width (n = 50). Its ultrastructure is characteristic of monokaryotic groups. All lifecycle stages of the pathogen, including meronts, sporonts, sporoblasts, and mature spores, are monokaryotic. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In Turkey, the microbial control of E. kuehniella has been focused on the spore-forming bacterium, Bacillus thuringiensis (Azizoğlu et al 2011b). There is no record on naturally occurring entomopathogenic protists of E. kuehniella in Turkey although several protists have been isolated from insects (Yaman et al 2016 and2019). The neogregarine presented here was the first one isolated from this pest in Turkey.…”
Section: Resultsmentioning
confidence: 89%
“…In Turkey, the microbial control of E. kuehniella has been focused on the spore-forming bacterium, Bacillus thuringiensis (Azizoğlu et al 2011b). There is no record on naturally occurring entomopathogenic protists of E. kuehniella in Turkey although several protists have been isolated from insects (Yaman et al 2016 and2019). The neogregarine presented here was the first one isolated from this pest in Turkey.…”
Section: Resultsmentioning
confidence: 89%
“…Larvae develop during the summer and in the end of August, the new generation appears (Urban, 2011). Yaman et al (2019a) observed heavily infected midgut addition to gut, Malpighian tubules, haemolymph, silk glands, and adipose body in C. aurata adults, but they did not mention reproductive organs. Spores of microsporidia infecting the digestive tract are commonly disseminated in faeces (Weiser, 1961;Becnel and Andreadis, 1999).…”
Section: Discussionmentioning
confidence: 92%
“…Studies on any natural enemies of this pest, suppressing its populations naturally, are of great interest for biological control. However, there are very limited studies on the entomopathogenic organisms of C. aurata for biological control (Yaman and Ertürk, 2016;Yaman et al, 2015Yaman et al, , 2019a. Recently, Yaman et al (2015) found 2 types of microsporidian pathogens infecting this pest for the first time and later the pathogens were identified as Microsporidium sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sycophanta adults and T. pityocampa larvae were collected in the rearing laboratories in Agean and Mediterranean region of Turkey. Samples of both insects were dissected in Ringer's solution (Merck) for microscopic examination according to Yaman (2019). The midgut lumen of C. sycophanta and the different organs such as intestine, fat body, hemocoel and Malpighian tubules of T. pityocampa were examined for the occlusion bodies (OBs) of T. pityocampa cypovirus.…”
Section: Methodsmentioning
confidence: 99%